Avaliação de programas educacionais para gestão: um estudo de caso avaliativo no Grupo Carmehil em Fortaleza-CE - Parente, Francisco de Assis Camelo (2015)
Assessment of Management Educational Programs: an evaluative case study in the Carmehil Group in Fortaleza established as research problem the issue of: “How to apply, in a participatory manner, an evaluative study of educational programs for management development based on dialogue?” The overall objective of the present work consists of carrying out an evaluative study of educational programs for management development based on dialogue that is able to minimize the difficulties of existing programs, detected among social actors. And, as specific objectives the study aims to: “Analyze the effectiveness of the management development program under study; identify and analyze the weaknesses and difficulties of the educational program under study; and develop an assessment process based on the dialogue with the social actors involved”. The work adopts the four pillar methodological strategy of De Bruyne, Herman and De Schoutheete (1977) in the field of educational assessment, from four different integrated views: Epistemological, theoretical, morphological and technical. The epistemology is based on the philosophical hermeneutics of Gadamer (2012a, 2012b), in educational assessment and humanism. The theory is grounded on the humanism of Rogers (1977a, 197b), on the educational assessment in Stake (2006), Parlett and Hamilton (1982), and Saul (1988); and on the business education in Maslow (1962), McGregor (1999), Herzberg e Mausner (1964) and Simon (1965). The morphological pillar features the assessment models of the theoretical basis. As for the technical pillar, the work adopts a mixed approach – primarily qualitative, without disregarding quantitative data. It is an evaluative case study of a "Strategic Program of Management Development – PEDG" of the Carmehil Group, and the participants are members of the technical coordination, teachers and students of the Program. Questionnaires with open and closed questions, participant observation, document analysis and semistructured interviews were carried out, using the recorder as to secure the ethical aspects of the research. The PEDG students showed clear awareness of humanistic aspects of their managerial roles despite reproducing traditional models. It is believed that the figure of the manager / facilitator who can himself/herself develop personal attributes that create the conditions for developing employees’ potential is missing. The manager / facilitator encourages each person to seek dialogue, ask questions, listen to people, respect them in this process in an open relationship that fosters the expression of feelings in an atmosphere of human solidarity. Companies today need to seek a group experience that can generate not only economic and social results but emotional results as well – people deal with people and people are made of emotions and these need to be fostered so as to generate an atmosphere of mutual trust. And carrying out an evaluative study of a management development program based on dialogue involves going through the process of educational assessment with a focus on mediate evaluation.